Pendidikan Kewarganegaraan: Membangun Sekolah Damai Untuk Wujudkan Lingkungan Masyarakat Aman dan Sejahtera - Sukron Mazid; Anif Istianah (Al-I'timad: Jurnal Dakwah dan Pengembangan Masyarakat Islam, 2023)
Citizenship Education (PKn) plays an important role in developing a peaceful school environment and contributing to the formation of a socially prosperous society. PKN teaches students critical and analytical thinking skills, preparing them to address social problems with wise solutions and focus on achieving peace. This type of qualitative research uses a library approach, data sources consist of literature sources by selecting book and journal references that have a relationship with diversity during the pandemic. Data collection techniques use documentation and observation studies. The research results show that Civics can form a young generation who is aware of the importance of cooperation, tolerance and peace in everyday life. Civics has a crucial role in forming peaceful schools that contribute to the welfare of social society.